PENGEMBANGAN MATERI AJAR DAN EVALUASI PADA KETERAMPILAN MENDENGARKAN DAN MEMBACA - Iswara, Prana D. (Universitas Pendidikan Indonesia, 2016)
Some of the receptive language skills are listening and reading skills. Curriculum (Indonesian Curriculum 2006, 2013, or 2016 revision) is a standard curriculum used by teachers in the school. Learning to listen assessed on the ability of students retold orally or in writing Learning reading rated from revealing reading materials orally or in writing Listeners and reader's comprehension must be equal to the intended speaker and author. Receptive expression in its evaluation involves the expressive ability (speaking and writing) to revive the gathering and reading. Evaluation of the learning listening and reading could have been a test, performance test, project or portfolio.Keywords: learning materials, evaluation, listening, reading.